A Comparative Study on Automatic Financial Exchange between Indonesia and Malaysia - Bambang Sugeng Ariadi Subagyono; Agus Yudha Hernoko; Zahry Vandawati Chumaida (Rechtsidee, 2019)
Taxpayer data and information from banking and finance institution could be guidance on any development. Therefore, it could be a corrective act to do the law enforcement on increasing Inland Revenue. Financial information exchange regarded to tax interests, besides by demanding way also could automatically way done (Automatic Exchange of Financial Account Information/AEol). Indonesia commitment was manifested by Multilateral Competent Authority Agreement signed after AEOI on 3rd June 2015. Indonesia agreed to start the financial information exchange automatically on September 2018. The followed-up Indonesia government commitment was on 8th May 2017. It had approved the financial information access no.1 2017 legislations as to tax interests. Then, one year later was set to be no.9 2017 legislations.